Whitening Dentifrices Effect on Enamel with Orthodontic Braces after Simulated Brushing - Torres, Vivian Santos (Eur J Dent, 2020)
Objective  This study aimed to evaluate in vitro the effects of whitening dentifrices on enamel color, the shear bond strength of orthodontic brackets and adhesive remnant index (ARI). Materials and Methods  Eighty bovine teeth with brackets were randomly divided into four groups ( n = 20): control group (GC)–water, test group 1 (GT1)–Colgate Total 12, test group 2 (GT2)–Curaprox Black Is White, and group test 3 (GT3)–Luminous White. All groups were submitted to brushing, simulating 12 months. The specimens were exposed to spectrophotometer color evaluation and to a shear strength test in a universal test machine using a 300 kN load with a crosshead speed of 0.5 mm/min. The ARI was evaluated with a stereoscopic magnifying glass. Statistical Analysis  Nonparametric Kruskal–Wallis and Dunn’s tests were used for the color analysis, and Friedman and Nemenyi tests were used to compare the times in the variable. To compare the shear force between the groups, the data were evaluated by one-way analysis of variance and Tukey’s test, and ARI was analyzed using Fisher’s exact test, always with a significance level of 5%. Results  In the color analysis, GT3 presented the greatest progression in whitening effect. GT1 had greater shear strength than GT3 did ( p ≤ 0.05). For ARI, the score 1 was predominant in the GC and GT1. The GT2 and GT3 groups had scores of 3. Conclusion  The whitening dentifrices promoted significant color change over the 12-month brushing time and may have interfered in the resistance to shear bond strength and ARI.